PENANAMAN SIKAP PEDULI LINGKUNGAN DAN SIKAP ILMIAH SISWA SEKOLAH DASAR MELALUI SOSIALISASI PROGRAM SEKOLAH PEDULI DAN BERBUDAYA LINGKUNGAN - Ratna Widyaningrum Anggit Grahito Wicaksono (Universitas Slamet Riyadi, 2018)
This community service aims to (1) provide understanding in the preparation oflearning tools that are integrated with environmental education, (2) socialize innovativeprograms as an effort to realize the school’s cares and cultured environment, and (3)inculcate the attitude of environmental concern and scientific attitude to students ofelementary school. The place of the community service is done in SDN Prawit I No. 69Surakarta. Methods of implementation of community service include: (1) the approachmethod undertaken from the survey, licensing and motivation stages for the teacher to betrained (2) the method of program implementation, including the preliminary stage, thesocialization and audience stage, the implementation stage and the final evaluation stage.The expected output targets is the teacher who attended this training is able to arrangelearning tools and able to realize the program to the school’s cares and culturedenvironment. The resulting output is educational environment-oriented learning tools,Green Club's extracurricular design, implementation program in realizing a caring andcultured school environment, and publication of community service articles in scientificjournals. Based on the dedication that has been done, the teachers feel interested and startdesigning environmentally oriented learning tools, schools have implemented clean andhealthy life behaviour, and start running programs to adiwiyata school.Keywords: Environmental Concern Attitude, Scientific Attitude, School’s Care and CulturedEnvironment.